2016
DOI: 10.1128/jvi.02810-15
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Detargeted Mengovirus for Oncolytic Virotherapy

Abstract: Mengovirus, a member of the Picornaviridae family, has a broad cell tropism and can cause encephalitis and myocarditis in multiple mammalian species. Attenuation has been achieved by shortening the polycytidine tract in the 5′ noncoding region (NCR). A poly(C)-truncated strain of mengovirus, vMC24, resulted in significant tumor regression in immunocompetent BALB/c mice bearing syngeneic MPC-11 plasmacytomas, but the associated toxicities were unacceptable. To enhance its safety profile, microRNA target sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 58 publications
0
63
2
1
Order By: Relevance
“…Despite the fact that our data indicate that insertion of miR‐TS into the viral genome per se slightly impairs virus replication and cytotoxicity, the site of miR‐TS insertion is an additional crucial factor affecting silencing of the virus by the corresponding miRs. The genomic structure of picornaviruses can be divided into a 5′‐UTR, the protein coding region, and a 3′UTR, and previously it was shown that CVB3 with miR‐TS in the 5′‐UTR and in the 3′UTR are susceptible to their corresponding miRs . On the other hand, it has also been shown that certain sections within the 5′‐UTR and 3′UTR do not tolerate miR‐TS insertion, most likely because insertion of miR‐TS disturbed higher‐order RNA structures of the viral genome .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that our data indicate that insertion of miR‐TS into the viral genome per se slightly impairs virus replication and cytotoxicity, the site of miR‐TS insertion is an additional crucial factor affecting silencing of the virus by the corresponding miRs. The genomic structure of picornaviruses can be divided into a 5′‐UTR, the protein coding region, and a 3′UTR, and previously it was shown that CVB3 with miR‐TS in the 5′‐UTR and in the 3′UTR are susceptible to their corresponding miRs . On the other hand, it has also been shown that certain sections within the 5′‐UTR and 3′UTR do not tolerate miR‐TS insertion, most likely because insertion of miR‐TS disturbed higher‐order RNA structures of the viral genome .…”
Section: Discussionmentioning
confidence: 99%
“…In picornaviruses, the site of miR-TS insertion within the viral genome seems to be a further aspect critically influencing virus suppression. Previous published studies successfully inserted miR-TS within the 5 0 and 3 0 UTRs of the viral genome [14,23,27]. However, it has also been shown that certain sections within the 5 0 UTR and the 3 0 UTR do not tolerate miR-TS insertion [28].…”
mentioning
confidence: 99%
“…Mengovirus (another member of Picornaviridae) has also been shown to infect and kill MM cells; however, in vivo studies with this virus demonstrated only modest efficacy along with relatively high toxicity. 134 Coxsackie viruses are positive-sense, single-stranded RNA viruses, which means their nucleic acid is directly infectious. In an interesting study, Hadac et al were able to demonstrate that injection of infectious A21 nucleic acid into solid MM plasmacytomas initiated an oncolytic infection with efficacy similar to that seen using intact virus.…”
Section: Picornavirusmentioning
confidence: 99%
“…The utility of this method for regulating viral tropism was originally demonstrated in lentiviral vectors to restrict transgene expression in specific tissues 14,15,16 . This technique has subsequently been applied to a vast array of replicating and non-replicating viral vectors for enhanced gene therapy as well as to improve the safety profiles of many oncolytic viruses by eliminating undesired toxicities in normal tissues 10,11,12,13,17 . It has also been utilized to generate safe and effective live-attenuated vaccines as well as to improve virus and vaccine manufacturing processes 18,19,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…This technique does not introduce new tropisms for the virus and therefore does not introduce any new safety concerns. Additionally, this method can be used to regulate multiple tropisms simultaneously by using target sequences for multiple different microRNAs enriched within different cell types 16,17,57,58,59,60,61 . This can all be accomplished without attenuating the virus in cells that do not express the corresponding microRNAs and therefore can provide a mechanism for improving the safety of therapeutic viruses with enhanced potency.…”
mentioning
confidence: 99%